Comportamiento cinético de la variación de vitamina c en pulpa concentrada de mango (mangifera indica l.) Variedad Haden y Kent - Manayay S, Damián (2014)
Faced with the problem of the lack of proper management of degradation parameters of organoleptic and nutritional quality thermal and storage of mango pulp process, has been modeled the kinetic behavior of the degradation of vitamin C in the thermal process pulp concentrated (28 ° Brix) and Haden mango variety Kent, exposing samples at temperatures of 80, 85, 90, 95 and 98 ° C, and for times of 0, 30, 60, 90, 120, 150, 180, 210 and 240 minutes respectively. The analysis of the results using statistical models theorists first and secondorder fit through the software Statgraphics Centurion XV, revealed with a probability of error of 5%, the degradation of vitamin C concentrated mango pulp both Haden variety and Kent, is adequately described by a kinetic first-order reaction, where the ranges of variation of the kinetic constant